OPTIMIZATION OF ELECTRICAL INSTALLATIONS FOR ENERGY EFFICIENCY IN SCHOOL BUILDINGS USING ENERGY-EFFICIENT LIGHTS - Zuraidah Tharo; Siti Anisah; M. Rizki Liano (Yayasan Sinergi Multidimensi Kreatif, 2025)
The need for electrical energy in the education sector continues to increase along with the development of technology and teaching and learning activities that require optimal lighting. This research aims to study and optimize electrical installations in school buildings through the application of energy-saving lights as an effort to improve electricity consumption. The methods used include analyzing the existing conditions of electrical installations, identifying the type and number of conventional lamps used, and calculating potential energy savings and costs after replacement with energy-saving lamps such as LEDs. The results show that the use of energy-efficient lamps can reduce electricity consumption by 40–60% compared to incandescent lamps or CFLs. In addition, resetting the installation layout as well as the use of automatic sensors can also improve user efficiency and comfort. Thus, optimizing electrical installations through the application of energy-efficient lights has proven to be effective in reducing electricity load and school operational costs, as well as supporting the creation of an energy-friendly educational environment